Explosive Performance Assessment of Buried Steel Pipeline - Seyed-Mohammad Seyed-Kolbadi (Advances in Civil Engineering, 2021)
It is so important to consider the passive defense problem in any places there have been attacks by varies kinds of military threats and terrorists. It is certain that social security is related to overcoming on these perils and protection from country. Vital facilities are one of examples that should be protected. Vital facilities include roads, bridges, transmission lines, and telecom and media network. With attention to the intense dependent to export and transmit of oil and gas and with consideration of this point that many places are full of gas and oil resource, the protection of these lines is very important. In recent years, occurrence of varies kinds of terrorist accidents in relation to important structures in all the world causes that the explosion loads have special attention. Explosion can generate much damage with vibration in vast soil media. Thus, it is important to predict the dynamic impact load and its treatment response. With attention to regardable development of numerical methods in recent decades, it is possible to investigate the explosion effects on surface and underground structures. In this research, the newest applied method modeling of the explosion phenomenon has been investigated and comprehensive information has been earned. In this investigation, problem of explosion wave’s propagation effects on buried pipes simulated by ABAQUS/CAE 6.10-1 was studied based on the finite element method. Surface explosion effects on gas buried pipe lines and their dynamic response have been investigated depending on properties and their characteristics. The variation of buried pipe depth effects and variation effects in soil properties around pipe in different cases has been considered, and the results are here. The results showed that in buried pipes under surface explosions, displacements, major stresses, and strains decrease in clay, dense, and loose sands with increase of buried depth. These results obtain that because of increase of closuring of pipes in soil when internal friction angle increases for a kind of soil, the stress on pipe rim will decrease also. It was also observed that the pipe performance in clay and loose sands is better than that in compacted sand, respectively.